2014
DOI: 10.1177/1040638714538965
|View full text |Cite
|
Sign up to set email alerts
|

Detection and genetic characterization of Canine parvovirus and Canine coronavirus strains circulating in district of Tirana in Albania

Abstract: An epidemiological survey for Canine parvovirus 2 (CPV-2) and Canine coronavirus (CCoV) was conducted in Albania. A total of 57 fecal samples were collected from diarrheic dogs in the District of Tirana during 2011–2013. The molecular assays detected 53 and 31 CPV- and CCoV-positive specimens, respectively, with mixed CPV–CCoV infections diagnosed in 28 dogs. The most frequently detected CPV type was 2a, whereas IIa was the predominant CCoV subtype. A better comprehension of the CPV–CCoV epidemiology in easter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
24
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 21 publications
4
24
1
1
Order By: Relevance
“…The present study represents the first 10‐year molecular survey for carnivore parvoviruses conducted on domestic and wild carnivores in Bulgaria. The obtained findings, indicating a higher frequency of CPV‐2a in Bulgarian dogs, are in agreement with the results from recent studies in other countries of the Balkan peninsula, such as Albania and Greece (Ntafis et al., ; Cavalli et al., ). Only five samples were positive for CPV‐2c (one for the 2004–2010 period), despite the widespread distribution of this virus in western Europe (Decaro and Buonavoglia, ,b) and the continuous import of dogs in Bulgaria from this area.…”
Section: Discussionsupporting
confidence: 92%
“…The present study represents the first 10‐year molecular survey for carnivore parvoviruses conducted on domestic and wild carnivores in Bulgaria. The obtained findings, indicating a higher frequency of CPV‐2a in Bulgarian dogs, are in agreement with the results from recent studies in other countries of the Balkan peninsula, such as Albania and Greece (Ntafis et al., ; Cavalli et al., ). Only five samples were positive for CPV‐2c (one for the 2004–2010 period), despite the widespread distribution of this virus in western Europe (Decaro and Buonavoglia, ,b) and the continuous import of dogs in Bulgaria from this area.…”
Section: Discussionsupporting
confidence: 92%
“…Sagazio et al, 1998;Truyen et al, 2000;Buonavoglia et al, 2000;Pereira et al, 2000). The newest variant CPV2c, often associated to severe disease in adult dogs including those that have completed the vaccination protocols, it is becoming prevalent in different geographic regions, and this is the case in Argentina (Martella et al, 2004;Nakamura et al, 2004;Kapil et al, 2007;Decaro et al, 2007Decaro et al, , 2009aDecaro et al, ,b, 2013Hong et al, 2007;Perez et al, 2007;Joao Vieira et al, 2008;Calderon et al, 2011Calderon et al, , 2009Nandi et al, 2010;Ntafis et al, 2010;McElligott et al, 2011;Filipov et al, 2014;Cavalli et al, 2014).…”
Section: Introductionmentioning
confidence: 93%
“…Recent epidemiological reports indicate that CPV-2a with VP2 426Asn is the predominant variant in Australia (Meers et al, 2007), most of Asian (Yoon et al, 2009, Phromnoi et al, 2010Chou et al, 2013;Yi et al, 2014;Timurkan et al, 2015) and European countries (Ntafis et al, 2010;Decaro et al, 2011Decaro et al, , 2013Cavalli et al, 2014;Filipov et al, 2014), and this is the only variant reported in New Zealand (Ohneiser et al, 2015), Nigeria (Dogonyaro et al, 2013), Hungary (Demeter et al, 2010), Czech Republic , Slovenia and Romania (Decaro et al, 2012), while it was not detected in Vietnam and Mexico, as well as, from an outbreak in a litter in Sweden (Table 1, Fig. 4).…”
Section: The Worldwide Distribution Of Antigenic Cpv-2 Variants Spreamentioning
confidence: 99%